From individual choices to the 4-eyes-principle: The big robber game revisited among financial professionals and students - Sebastian Bachler; Armando Holzknecht; Jürgen Huber; Michael Kirchler (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2024)
While headline news frequently report cases of large-scale fraud, corruption, and other immoral behavior, laboratory experiments often show prosocial behavior in strategic games. To reconcile and explain these seemingly conflicting observations, Al'os-Ferrer et al. (2022) introduced the Big Robber Game-an altered dictator game where one robber can take money from multiple victims. They reported low prosocial behavior among a pool of student subjects who behaved more prosocial in bilateral games than in the Big Robber Game. In our study, we employ the Big Robber Game within a 2x2 factorial design, engaging over 860 participants to examine the behaviors of financial professionals versus students. Moreover, inspired by the four-eyes principle, a common practice in the finance industry, we investigate decision-making both individually and in pairs. We find overall support for the results of Al'os-Ferrer et al. (2022) and that finance professionals rob less than students. Accounting for a multitude of specifications, socio-demographic characteristics and individual preferences, we report that treatment differences disappear, indicating similar behavior across individuals, pairs, finance professionals, and students. Finally, in a series of non-pre-registered exploratory analyses, we show that victims expect finance professionals to rob significantly more than student robbers, implying that finance professionals are considered to be less pro-social than students' peers.
Keywords: C91; C93; D91; 330; Selfishness; Social Preferences; Finance Professionals; Group decisions; Experimental Finance